2021
DOI: 10.3390/app11114797
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Growth, Physiology, Yield, and Quality of Wheat under the Application of Different Zinc Coated Formulations

Abstract: Zinc (Zn) is critical for the activity of many enzymes including involved photosynthetic CO2 fixation and indirectly involved in the production of growth hormones and internode elongation in crop plants. In this regard, a field experiment was conducted to investigate the comparative effectiveness of the Zn blended, Zn coated and bio-activated Zn coated urea on the growth, physiological, yield, and quality of wheat. Three types of urea were prepared including bio-activated Zn coated, Zn coated and Zn blended ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Nitrogen (N) is the basic component of chlorophyll molecules and is necessary for its production in plants. As such, these minerals help the bacteria to live and the plant to grow sustainably [67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen (N) is the basic component of chlorophyll molecules and is necessary for its production in plants. As such, these minerals help the bacteria to live and the plant to grow sustainably [67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…The application of Zn fertilizer, such as zinc sulfate (ZnSO 4 ), is a quite effective method to correct the deficiency of Zn and further improve in grain yield and increase grain Zn concentration ( Khan et al, 2003 ; Rehman et al, 2018 ). Zn application methods mainly include soil application, foliar application, seed priming, and seed coating ( Nadeem and Farooq, 2019 ; Nazir et al, 2021 ). Recent research has found that the application of 5–45 kg ZnSO 4⋅ 7H 2 O ha –1 to the soil increased grain yield (13–60%) ( Khan et al, 2002 ; Huang et al, 2019 ), while foliar application seems more effective in boosting grain Zn concentration ( Fageria et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The application of Zn fertilizer, such as zinc sulfate (ZnSO 4 ), is a quite effective method to correct the deficiency of Zn and further improve in grain yield and increase grain Zn concentration (Khan et al, 2003;Rehman et al, 2018). Zn application methods mainly include soil application, foliar application, seed priming, and seed coating (Nadeem and Farooq, 2019;Nazir et al, 2021). Recent research has found Abbreviations: TN, soil total nitrogen; AN, soil available nitrogen; TP, soil total phosphorus; TK, soil total potassium; CEC, soil cation exchange capacity; SOC, soil organic carbon; AZ, soil available zinc; PCoA, principal coordinate analysis; RDA, redundancy analysis; LEfSe, linear discriminant analysis effect size; LDA, linear discriminant analysis; OTU, operational taxonomic unit; HHZ, NJ908 and ND9925, Huanghuazhan (Japonica rice), Nanjing-9108 (Japonica rice), and Nuodao99-25 (glutinous rice); ZS0 and ZS2, treatments without added basal zinc fertilizer and with basal zinc fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…The use of nitrogen in combination with zinc, such as zinc-coated urea, minimizes the negative effects of high temperatures in plants to a certain extent (Raj et al, 2015). Heat stress in plants may be alleviated by providing Zn through Zn-coated urea, which boosts Zn levels in various plant sections; Zn increases ABA concentration, which in turn, strengthens the plant's defense system (Nazir et al, 2021). The kinetics of Zn-coated urea in the soil is altered by high temperatures, which has a detrimental impact on ZnCU efficiency (Nazir et al, 2021).…”
Section: E Ect Of Temperature On Availability Of Coated Ureamentioning
confidence: 99%
“…Zinc-coated urea increased grain yield by around 28% and is quite effective toward plant physiological attributes (Nazir et al, 2021). As compared to prilled urea, 29% of rice production was increased by the use of zinc-coated urea (Shivay et al, 2019).…”
Section: Enhancement Of Yield Through the Application Of Nutrient-coa...mentioning
confidence: 99%